Case Report: The Effect of 25% Podophyllin Tincture in Condylomata Accuminata - Lita Setyowatie; Ayunita Mayasari (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2023)
Introduction: Condylomata accuminata (CA) is one of the most common sexually transmitted infections in the genital area caused by Human Papilloma Virus (HPV) variants 6 and 11. This disease is also known as genital warts. The potential for recurrence is relatively high and the risk for malignancy is high, therefore it requires appropriate treatment and therapy. There is no clear evidence regarding the best treatment choice for patients with CA. Case Presentation: Female, 24 years old with complaints of genital warts that have grown bigger since 1 month before. Physiological examination of the labia minora showed multiple papules with mucosal-like color and verrucous surfaces, varying in shape and size. The acetowhite test result was positive. Patients were treated with 25% podophyllin tincture, with an interval of one week one time. Conclusion: Podophyllin usage as a therapy for CA provides excellent therapeutic response and is relatively affordable, simple, and has minimal side effects. Patients treated with 25% podophyllin tincture, with an interval of one week one time, for two weeks showed significant improvement of the lesions.